Pudicinae (Nematoda) coparasitic in Proechimys roberti (Rodentia: Echimyidae) from the Brazilian Amazonia: description of a new species of Pudica, redescription of Pudica evandroi (Travassos) and updated key to the species of the genus - Serrano, Paula Carolina (2019)
The re-examination of nematodes collected decades ago from a spiny rat, Proechimys roberti (Echimyidae) from Para State, revealed the presence of Acanthostrongylus acanthostrongylus Travassos, 1937, and two coparasitic species of Pudica (Heligmonellidae: Pudicinae), one of them new to science. Pudica minima n. sp. mostly resembles Pudica tenua Durette-Desset, 1970, described from Proechimys semispinosus in Colombia. Nevertheless, it differs from P. tenua by having a synlophe with 12 ridges with poorly developed careen, bursal pattern of type 2-2-1 on the right lobe, bursal rays 2 and 3 similar in length, and spicules longer with spoon-shaped tips. Pudica evandroi (Travassos, 1937) was already described from Pr. roberti but its synlophe remained undescribed and the original description lacked some details. A detailed study of the synlophe is provided and the range of morphometric data for males and females is enlarged. The study of the synlophe allowed ratifying the placement of this species within Pudica, as early suggested by previous authors. The species list and identification key to species of Pudica are updated with the inclusion of three species. The status of Heligmosomum alpha Travassos, 1918, which was transferred to Pudica in 1990, is emended and the species is considered a Nippostrongylinae incertae sedis.